2014
DOI: 10.1186/1742-2094-11-18
|View full text |Cite
|
Sign up to set email alerts
|

CD80+ and CD86+B cells as biomarkers and possible therapeutic targets in HTLV-1 associated myelopathy/tropical spastic paraparesis and multiple sclerosis

Abstract: BackgroundHuman T-cell lymphotropic virus (HTLV-1) is the causative agent of the incapacitating, neuroinflammatory disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Currently, there are no disease-modifying therapies with long-term clinical benefits or validated biomarkers for clinical follow-up in HAM/TSP. Although CD80 and CD86 costimulatory molecules play prominent roles in immune regulation and reflect disease status in multiple sclerosis (MS), data in HAM/TSP are lacking.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 129 publications
2
29
0
Order By: Relevance
“…The host's immune response against HTLV‐1‐infected T‐cells is induced by CTLs in the central nervous system, resulting in the production of Th1 cytokines such as IFN γ, IL‐2, and TNF‐α by activated cells, which leads to the destruction of neurons [Espíndola et al, ]. Expression of pro‐inflammatory IFN γ is intensified in HAM/TSP patients and ACs compared to healthy people [Menezes et al, ]. In addition to these cytokines, in the present study the expression of IFN λ3 was evaluated in both sets of patients.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The host's immune response against HTLV‐1‐infected T‐cells is induced by CTLs in the central nervous system, resulting in the production of Th1 cytokines such as IFN γ, IL‐2, and TNF‐α by activated cells, which leads to the destruction of neurons [Espíndola et al, ]. Expression of pro‐inflammatory IFN γ is intensified in HAM/TSP patients and ACs compared to healthy people [Menezes et al, ]. In addition to these cytokines, in the present study the expression of IFN λ3 was evaluated in both sets of patients.…”
Section: Discussionmentioning
confidence: 53%
“…The viral burden is presented as a section of PBMCs that comprise integrated proviruses (the so‐called PVL) [Niederer et al, ]. While the heterogeneity of the disease outcome is still unclear, it is probably specified by the interaction between viral and host immune factors such as Tax, HBZ, PVL, and the host's genetic and epigenetic characteristics and cytokines [Menezes et al, ]. Andrade et al [] found a drastic correlation between Tax and HBZ mRNA expression in HAM/TSP individuals and their linkage with various markers of the neurological disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results show that live Mtb is a potent stimulus to induce ISGs HSPCs require further investigation. Of note, in our previously characterized cohort of multiple sclerosis patients (Menezes et al, 2014;Van Weyenbergh, Wietzerbin, Rouillard, Barral-Netto, & Liblau, 2001), IFN-β therapy in vivo did not significantly change monocyte or lymphocyte counts, nor did it increase the ML ratio after three months of treatment in patients with documented clinical response (data not shown), supporting the idea that type I IFN by itself is not sufficient to cause monocyte expansion in vivo.…”
Section: Discussionmentioning
confidence: 56%
“…If our finding is true and there actually is a repeatable difference between men and women in CD86 expression on some B cell subtypes, our data indicate that these differences are found in more mature cell sybtypes, PB versus pre-PB, and SM and NSM versus DNM. One previous study describes a clear sex dependent difference in CD80 expression on B cells in neuroinflammatory diseases, independent on disease severity [26]. There is a CD86 polymorphism resulting in higher CD86 expression on B cells [27], and it cannot be excluded that there was an increased frequency of men with that allele in our cohort.…”
Section: Discussionmentioning
confidence: 65%